Effects of cultivated wild ginseng pharmacopuncture on lowering lipid and oxidative capacity in biochemical and molecular biological study in obese rats - Eun Ju Choi; Joon Moo Lee; Seung Hwan Won; Ki Rok Kwon (Korean Pharmacopuncture Institute, 2006)
Objectives : This study was carried out to identified the effects of distilled cultivated wild ginseng pharmacopuncture to the obesity. Methods : Cultivated wild ginseng pharmacopuncture was administered on the points of chung-wan(CV12), Ch'ŏnch'u(ST25), and Chok-samni(ST36) on lowering lipid and oxidative capacity in biochemical and molecular biological aspects were investigated in obese rats fed with high fat diet. Results : 1. The contents of plasma β-lipoprotein showed a tendency to decrease in the pharmacopuncture groups compared to the control group. In the pharmacopuncture groups, the values of ST25 and ST36 pharmacopuncture groups showed lower value. 2. The contents of plasma free fatty acids showed a tendency to decrease in pharmacopuncture groups compared to the control group. However, in the pharmacopuncture groups, the values were not significantly different. 3. Plasma triglyceride and glucose showed lower value in the ST25 pharmacopuncture groups compared with the other groups. 4. The activity of AST showed a tendency to decrease in the pharmacopuncture groups. However, the activity of ALT was not significantly different in all the treatment groups. 5. Plasma total cholesterol and LDL-cholesterol showed lower value in the ST25 and ST36 pharmacopuncture groups and HDL-cholesterol showed higher value in the CV12 pharmacopuncture groups than that of the other treatment groups. 6. Liver total cholesterol values didn't show significant difference in all the treatment groups, and triglyceride showed lower value in the pharmacopuncture groups. 7. The contents of plasma TBARS showed lower value in the ST25 pharmacopuncture group and contents of liver TBARS showed a tendency to decrease in the pharmacopuncture groups. However these values didn't show significant difference in the pharmaco puncture groups. 8. Liver super oxide dismutase activity showed higher value in the ST25 and ST36 pharmacopuncture groups, and the value of liver glutathione peroxidase and catalase activity showed a tendency to increase in the pharmacopuncture groups. However, these values showed no significant difference in the pharmacopuncture groups.9.Expression of apo-B and E mRNA in liver cells was lower in the ST25 pharmacopuncture group than that of the other treatment groups. However, expression of TNF-α and leptin mRNA in adipose cell showed no difference among all the treatment groups.10. ST25 pharmacopuncture group showed a good histological character of liver. It showed similar to that of normal group. However other treatment groups and control group showed slight vasodilation and slight fat accumulation. Conclusion : These results indicate that distilled cultivated wild ginseng pharmacopuncture suppressed adipose tissue mass and lipid peroxidation, and increased antioxidant capacity.